Colonic Epstein-Barr Virus-Associated Mucocutaneous Ulcer Associated With Ulcerative Colitis. Issue 2 (10th February 2023) - Chan, Patrick P.Y.; Farzin, Mahtab; Acharya, Priya; Viiala, Nicholas; Gilmore, Andrew; Crane, Harry; Henderson, Christopher; Ng, Watson; Williams, Astrid; Connor, Susan J.
ABSTRACT: Epstein-Barr virus-associated mucocutaneous ulcer is a rare lymphoproliferative disorder that occurs in immunosuppressed states that can develop in the gastrointestinal tract and mimic inflammatory bowel disease or other malignancies. We present the case of a 61-year-old man who presented with concurrent acute severe ulcerative colitis and colonic Epstein-Barr virus-associated mucocutaneous ulcer requiring rituximab therapy and a subtotal colectomy.